Phytothermotherapy with fermenting alpine grass in knee osteoarthritis: mid-long term results - P. Bortoli; A.M. Mariani; R. Bortolotti; F. Bonella; S. Inchiostro; P. Manica; R. Albertazzi; G. Paolazzi; R. Miori (PAGEPress Publications, 2011)
This is an observational study of the mid-long-term results of a single course of phytothermotherapy with grass baths (group A, 54 patients), of a course of usual medical care (group B, 58 patients) and of a course of physiokinesistherapy (FKT, group C, 30 patients) in knee osteoarthritis. For each group of consecutively treated patients we evaluated the Lequesne algo-functional Index, the drug consumption, the frequency of the patient-physician contacts and laboratory or radiological examinations after 10-15 days of treatment and at 3, 6, 9 and 12 months with blind telephonic follow-up. The mean Lequesne-score at basal time was 7.5±3.3, 11.9±5.3 and 11.0±2.7 in group A, B and C respectively. In each group this score diminished at the end of the treatment (p<0.001). At 3, 6, 9 and 12 months the score remained lower than at basal time in group A (p<0.001) and group B (p<0.01), but not in group C. Drug consumption, patientphysician contacts and lab examinations were 5 times lower in group A than in group B and group C at basal time and throughout the follow-up. The study underlines the mid-long term efficacy of grass baths on both pain and functionality in knee osteoarthritis; this effect, compared to basal values, was even more evident at 3 and 6 months than that of usual medical care. FKT shows improvement only at the end of the treatment, but not long-lastingly.